Air temperature and lapse rate variation in the ice‐free and glaciated areas of northern James Ross Island, Antarctic Peninsula, during 2013–2016. (23rd September 2018) - Ambrozova, Klara; Laska, Kamil; Hrbacek, Filip; Kavan, Jan; Ondruch, Jakub
Abstract : Studies assessing air temperature variations and their dependence on altitude from the eastern side of the Antarctic Peninsula are sparse. In this paper, we analyse air temperature and near‐surface lapse rates from the Ulu Peninsula (James Ross Island, Antarctic Peninsula). The temperature data were acquired from nine sites both in ice‐free areas and glaciers of the Ulu Peninsula in 2013–2016. The most important factors influencing air temperature differences were sea‐ice conditions, topography and ground surface properties. During the study period, air temperature decreased with height with the mean lapse rate of 0.40 °C 100 m −1 for the ice‐free sites (10–375 m a.s.l.) and 0.43 °C 100 m −1 for the glaciated sites (268–539 m a.s.l.). However, the values were lower in winter (ice‐free: 0.02 °C 100 m −1 and glacier: 0.31 °C 100 m −1 ) than in summer (ice‐free: 0.62 °C 100 m −1 and glacier: 0.51 °C 100 m −1 ) for both categories. The air layer between 10 and 56 m a.s.l. in the ice‐free area revealed an almost year‐round air temperature inversion resulting in a mean lapse rate of −0.79 °C 100 m −1 and an air temperature inversion frequency reaching up to 43%. The temperature inversion frequency was 10% lower for the lowest air layer for the glacier category, which was between 268 and 356 m a.s.l. The land surface air temperature was the highest when the wind was from the northwest and lowest when it was from the south–southwest. The near‐surface lapse rate–wind direction relationship was the most pronounced for the air layer between 10 and 56 m a.s.l. with the lowest mean lapse rate for west–southwest wind (−2.83 °C 100 m −1 ) and the highest for east–northeast wind (0.41 °C 100 m −1 ). Abstract : Spatial variability of air temperature on the Ulu Peninsula, James Ross Island, from 2013–2016 was analysed based on data from nine sites. The sites were divided into two categories (ice‐free and glacier sites) and each category was analysed separately. Special attention was given to the dependence on altitude by calculating near‐surface lapse rates and air temperature inversion relative frequency as well as to the effect of wind direction.